2000
DOI: 10.1046/j.1365-2427.2000.00553.x
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal changes in microbial assemblages of the Ogeechee River

Abstract: Summary Bacteria are common and important constituents of aquatic ecosystems but little is known about their populations; most measurements commonly employed are at a grosser, assemblage‐level. The purpose of this study was to compare longitudinal patterns in microbial assemblages and populations along a river ecosystem. Water samples were collected under base flow conditions from 13 main stem and four tributary sites along the Ogeechee River spanning the piedmont and coastal plain of Georgia, USA. Based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
21
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 39 publications
0
21
0
Order By: Relevance
“…In this study, we examined how different bacterial taxa in biofilms responded to DOM and inorganic nutrients by using nutrient diffusing artificial substrates (clay flowerpots), an approach commonly used to demonstrate nutrient limitation in streams (e.g., references 11 and 43). Responses to different treatments (leaf leachate [LL], glucose, algal exudates, and phosphate and nitrate singly and in combination) by different bacterial taxa and algae were compared among seasons.The bacterial taxa examined were selected because they are common in streams (21,25,26) and known to use a wide array of organic compounds (28). The three species targeted (Burkholderia cepacia, Acinetobacter calcoaceticus, and Pseudomonas putida) are gram-negative bacteria that are abundant in water and sediment (22).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, we examined how different bacterial taxa in biofilms responded to DOM and inorganic nutrients by using nutrient diffusing artificial substrates (clay flowerpots), an approach commonly used to demonstrate nutrient limitation in streams (e.g., references 11 and 43). Responses to different treatments (leaf leachate [LL], glucose, algal exudates, and phosphate and nitrate singly and in combination) by different bacterial taxa and algae were compared among seasons.The bacterial taxa examined were selected because they are common in streams (21,25,26) and known to use a wide array of organic compounds (28). The three species targeted (Burkholderia cepacia, Acinetobacter calcoaceticus, and Pseudomonas putida) are gram-negative bacteria that are abundant in water and sediment (22).…”
mentioning
confidence: 99%
“…The source, quality, and type of DOM, as well as the quantity, may influence the abundance and distribution of bacteria in stream ecosystems (20,21,24). In addition, other aspects of microbial community function such as respiration, biomass, and extracellular enzyme activity may be limited by dissolved inorganic nutrients and organic matter in streams (49, 51).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported dynamic changes, both spatially, within a watershed, and temporally, in the abundance and distribution of selected stream bacterial populations [11,12,[14][15][16][17]19]. However, differences in stream bacterial populations among watersheds from diverse regions exhibiting differing environmental conditions have not been examined [10].…”
Section: Introductionmentioning
confidence: 99%
“…In the Ogeechee River (GA, USA), P. putida numbers were higher and more consistent spatially than A. calcoaceticus numbers [11]. Likewise, on decomposing leaves in a stream, numbers of B. cepacia, A. calcoaceticus, and P. putida exhibited different responses [20].…”
Section: Introductionmentioning
confidence: 99%